Subcritical water treatment of bovine serum albumin pathway to produce superabsorbent biomaterial as green technology - Esfahan, Z. M.; Izhar, S.; Ismail, M. H. S.; Yoshida, H. (Elsevier, 2021)
Four different types of bovine serum albumin (BSA)-based biomaterials (BSA-based running gel, hydrogel, nanoparticles and two-phase) were formed in different subcritical water treatment (SCWT) conditions. In SCWT temperature range of 80–100°C the running BSA-based gels appeared which were distinguished by visual inspection. Stable hydrogel network can also form by SCWT without using any additives or cross-linking agent to yield superabsorbent hydrogels (SAHs) that were non-toxic. A detailed investigation of BSA-based biomaterials pathway under SCWT on the formation and reversible steps of these gels was carried out using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy. The optimum SCW gelation temperature of BSA hydrogels was found to lie between 100 and 120°C. All synthesized BSA-based superabsorbent hydrogels (BSAHs) showed a Fickian water diffusion mechanism and second order swelling kinetic model. Moreover, the initial water contents were 48, 46 and 41 g/g for BSAH100-9, BSAH110-9 and BSAH120-9 respectively. It could be found that, 44, 45 and 40% of trapped water retained from the swollen BSAH100-9, BSAH110-9 and BSAH120-9 respectively after 1 month, which is superior to that of any reported SAH. Remarkably, WRs still were more than 30% after 2 months, indicating super excellent water release capability of such BSAH. This good water release capability is ascribed to this novel structures of such BSAHs which had been prepared under SCWT. Overall, our approach demonstrates a rapid, crosslinker-free thermoresponsive BSA gelation approach with control on the material property, which is highly desirable in many applications such as drug delivery applications and agriculture.